The Holy-Erotic Spirituality: Merayakan Seksualitas, Menghidupi Spiritualitas - Timotius Verdino (Asosiasi Teolog Indonesia, 2021)
This article intends to show that spirituality and sexuality cannot be separated because they need one another and meet at a common point, namely eros which is animated by the Holy Spirit as a manifestation of divine eros or God's desire. To that end, this paper begins with a few explanations about human sexuality and an overview of how sexuality has been considered in Christianity throughout its history. After that, referring to the discussion of eros in the Song of Songs by Edmée Kingsmill and eros in the relation of the self and the Other according to Mayra Rivera, I will discuss eros as a meeting point for spirituality and sexuality. In the end, based on Pope Benedict XVI's view in Deus Caritas est, this article will be concluded with a theological construction of the Holy Spirit as the Divine Eros, which is God's own desire that animates both human spirituality and sexuality.